Categorical Perception of Mandarin Pitch Directions by Cantonese-Speaking Musicians and Non-musicians - Chen, Si; Yang, Yike; Wayland, Ratree (Frontiers in Psychology, 2021)
Purpose This study is to investigate whether Cantonese-speaking musicians may show stronger CP than Cantonese-speaking non-musicians in perceiving pitch directions generated based on Mandarin tones. It also aims to examine whether musicians may be more effective in processing stimuli and more sensitive to subtle differences caused by vowel quality. Method Cantonese-speaking musicians and non-musicians performed a categorical identification and a discrimination task on rising and falling continua of fundamental frequency generated based on Mandarin level, rising and falling tones on two vowels with 9 duration values. Results Cantonese-speaking musicians exhibited a stronger categorical perception of pitch contours than non-musicians based on the identification and discrimination tasks. Compared to non-musicians, musicians were also more sensitive to the change of stimulus duration and to the intrinsic F0 in pitch perception in pitch processing. Conclusion The categorical perception was strengthened due to musical experience and musicians benefited more from increased stimulus duration and were more efficient in pitch processing. Musicians might be able to better use the extra time to form an auditory representation with more acoustic details. Even with more efficiency in pitch processing, musicians’ ability to detect subtle pitch changes caused by intrinsic F0 was not undermined, which is likely due to their superior ability to process temporal information. These results thus suggest musicians may have a great advantage in learning tones of a second language.